Layered Electrodes Based on 3D Hierarchical Porous Carbon and Conducting Polymers for High‐Performance Lithium‐Sulfur Batteries. Issue 5 (20th March 2019) - Zeng, Shuaibo; Li, Xin; Zhong, Hai; Chen, Shaowei; Mai, Yaohua
Abstract: Easy dissolution of polysulfides and low loading of active materials are two major factors that limit the cathode cycling stability and energy density in lithium‐sulfur batteries. Herein, 3D hierarchical carbon with abundant pores is used for sulfur encapsulation (S@DHPC), which achieves a high sulfur content of 74 wt% and high sulfur loading of 5.8 mg cm −2 . Importantly, coating the obtained S@DHPC electrode with poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) conducting polymers is found to effectively impede the diffusion of polysulfide species, leading to marked improvement of the cycling stability of the electrode; and the electrode performance increases with an increasing number of the S@DHPC/PEDOT:PSS layer. For a three‐layer electrode, at a current density of 2 C, it delivers a discharge capacity of 846 mAh g −1 in the first cycle and maintains a capacity of 716 mAh g −1 after 500 cycles, corresponding to a fading rate of only 0.033% cycle −1 . Results from this study suggest that layered electrodes can be exploited as a unique electrode architecture for the fabrication of high‐performance lithium‐sulfur batteries. Abstract : To enhance cycling performance and increase sulfur loading of lithium‐sulfur batteries, three‐dimensional hierarchical porous carbon is used as a sulfur host. Coating of the sulfur‐loaded carbon electrode with conducting polymers leads to marked diminishment of the diffusion and loss of polysulfide species, and the performance as a lithium‐sulfur battery cathode increases with the number of the sulfur@carbon/polymer stacks.